Recommendations for the perioperative management of pancreatic and colorectal cancer patients - Vilz, Tim Oliver; Post, Stefan; Langer, Thomas; Follmann, Markus; Nothacker, Monika; Willis, Maria A. (Deutsches Ärzteblatt, 2024)
Malignant solid tumors of the gastrointestinal tract are among the more common types of cancer, with 117 000 new cases in Germany each year. Pancreatic and colorectal carcinomas (CRC) account for two-thirds of the cases (1). Despite the ongoing...
Gesehen am 26.03.2025